Cover Image. (22nd April 2020) - Hormazabal, Lorena; Correa, Flavia; Escribano, David; Quiroz, Gabriel; Saint‐Jean, Constanza; Espinel, Andrea; Diaz, Linder; Zambrano, Belkys; Galindo, Alberto; Viñals, Fernando
Abstract : The front cover image is based on the Original Article Feasibility and agreement of including anterior‐posterior complexes and landmarks of the proximal hemisphere into basic examination of the fetal brain: A prospective study by Lorena Hormazabal et al., https://doi.org/10.1002/pd.5652 .